PENGARUH PENILAIAN KINERJA DAN PENGEMBANGAN KARYAWAN TERHADAP PRODUKTIVITAS KARYAWAN (Kasus PT Bank Sumut, Cabang Sidikalang) - Bintang, Debbi H; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine the effect of performance appraisal and development of employees on work productivity of employees at PT Bank Sumut Cabang Sidikalang partially and simultaneously. Dimensions are used in performance assessment consists of a standard-setting work, performance assessment and provision of feedback. Dimensions variable employee development consists of materials, instructors and facilities. And dimensions for the independent variables (productivity of employees) consists of ability, morale, efficiency, improvement of work, quality, and self-development.The method used is descriptive analysis method, and multiple linear analysis method that produces output t test, F test, and test of the determinant (R²). Processing data using programe SPSS 20.The results showed that the partial performance appraisals significant effect on employee productivity PT Bank Sumut Cabang Sidikalang, partial variable employee development does not significantly influence employee productivity PT Bank Sumut Cabang Sidikalang, as shown by the significant value greater than 0, 05. And simultaneous assessment of performance and development of employees a significant effect on employee productivity. Based on research obtained the degree of correlation of 0.718 which indicates that the level of relationship between the independent variable on the dependent variable has a strong relationship and R² values obtained at 0.516 or 51.6%. This means that employee productivity PT Bank Sumut Cabang Sidikalang influenced by the performance appraisal and development of employees amounted to 51.6%.Keywords: Perfprmance Apraisal, Development Employee, Employee Productivity